2016
DOI: 10.1002/ptr.5738
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry: Chemical Profiling, in Vitro and in Vivo Antioxidant Activity and Nephroprotective Effect against Gentamicin Toxicity in Rats

Abstract: We assessed possible protective effect of bilberry diet in rat model of nephrotoxicity. In vivo and in vitro antioxidant activity and chemical profiling of this functional food was performed. With aid of HPLC-DAD and spectrophotometric method, 15 individual anthocyanins were quantified alongside total tannin, phenylpropanoid, and anthocyanin content. The study was conducted on four groups of rats: control, treated with only gentamicin, treated with only bilberry, and treated with both gentamicin and bilberry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
1
17
0
2
Order By: Relevance
“…Anthocyanin is a soluble pigment which is consisted naturally and belongs to flavylium cation structure [ 13 ]. Thanks to anthocyanins, bilberries have commonly biological effects such as anti-inflammatory, anticarcinogenic, antioxidant, and remaining normal physiological functions [ 14 , 18 ]. Antioxidant effect of bilberry was obtained by Bao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin is a soluble pigment which is consisted naturally and belongs to flavylium cation structure [ 13 ]. Thanks to anthocyanins, bilberries have commonly biological effects such as anti-inflammatory, anticarcinogenic, antioxidant, and remaining normal physiological functions [ 14 , 18 ]. Antioxidant effect of bilberry was obtained by Bao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin-induced nephrotoxicity is associated with an excessive formation of ROS and RNS [45]. Veljkovic et al [46] demonstrated that consumption of bilberry extract (100 mg/kg/day) for 15 days protected rats against gentamicin-induced nephrotoxicity by maintaining the activity of antioxidant enzymes. Likewise, consumption of edible berry mixture OptiBerry (20 mg/kg/week) (wild blueberry, bilberry, cranberry, elderberry, raspberry seeds and strawberry) for eight weeks significantly prevented hyperbaric oxygen-induced reduced glutathione (GSH) oxidation in the lung and liver of vitamin E-deficient rats [23].…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…So that the possibility of nephrotoxicity becomes a risk in the treatment using gentamicin. 2 Sterculia genus contains phenol compounds, flavonoids and their derivatives, terpenoids which are mostly as triterpenoids, coumarin, alkaloids and other compounds including phenolic acids, phenyl propanoids, fatty acids, sugars and some steroids. 3 Based on literature studies it is known that the primary production of secondary metabolites in the genus Sterculia is phenols and flavonoids.…”
Section: Introductionmentioning
confidence: 99%